The relationship between anxiety and depression with smartphone addiction among college students: The mediating effect of executive dysfunction - Ge, JiaMin; Liu, Ya; Cao, Wenjing; Zhou, Shuyin (Frontiers in Psychology, 2023)
Smartphone addiction symptom is increasing across the world. Many studies found that negative emotion is associated with smartphone addiction, but few studies explore the mediating effect of cognitive function. Through a large-scale cross-sectional survey conducted, 421 Chinese college students completed anxiety, depression, smartphone addiction, and executive dysfunction measures. We surveyed the prevalence of depression, impaired executive function, and smartphone addiction. The confirmatory factor analysis was performed on the questionnaire structure, and mediation models were used to examine the relationship between anxiety, depression, impaired executive function, and smartphone addiction.The main ﬁndings indicated that anxiety, depression, and executive dysfunction were positively signiﬁcant associated with smartphone addiction. Executive dysfunction played a mediated role between anxiety and depression with smartphone addiction. Speciﬁcally, executive dysfunction completely mediated the pathway of anxiety-smartphone addiction and partly mediated the path of depression-smartphone addiction. Depression directly positively predicted smartphone addiction, but anxiety did not. The sample is Chinese college students, which limits generalizability and self-reported lack of objectivity.The findings suggest that we should pay more attention to the mediating role of executive dysfunction between negative emotion-smartphone addiction.